Core competencies for physiotherapists working with refugees: a scoping review. (September 2020) - McGowan, Emer; Beamish, Nicole; Stokes, Emma; Lowe, Rachael
Abstract: Objective: To summarise the existing knowledge base that can inform the development of a core competency profile for physiotherapists to support and deliver rehabilitation services to refugees. Method: In this scoping review, a comprehensive search of peer-reviewed and grey literature was conducted. The search parameters included studies relevant to the physiotherapy profession and published between 2000 and 2019. MEDLINE, EMBASE, CINAHL, PEDro, and Ovid PsycINFO databases were searched. Grey literature was accessed through website searches, Google Scholar, and direct requests. Findings: Three themes were identified in the literature. The first theme encompassed the physical and mental health of refugees. The second theme explored the cultural competence physiotherapists need to work with refugees. This theme included the cultural influences on health and healthcare and communication strategies that could be used to optimise healthcare for refugees. The last theme described refugees and the healthcare system which encompassed the challenges that refugees face in accessing healthcare and navigating the healthcare system. The main physiotherapy competencies detected in the literature were an understanding of refugee health, the administration of culturally competent care and knowledge of healthcare systems as they relate to refugees. Conclusion: This comprehensive search identified three themes that can be used to inform the development of a competency profile for physiotherapists working with refugees. These themes are, however, rather vague and non-specific and signal the need for research to further examine the physiotherapy competencies necessary to provide the highest quality of care for this growing population.